Manipulation of the vegetative and reproductive cycle of pistachio (Pistacia vera L.) - Barone E.; La Mantia M.; Marra F.P.; Motisi A.; Sottile F. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
A study on the effects of Hydrogen-Cyanamide and urea treatments on pistachio (Pistacia vera L.) vegetative and reproductive cycles was carried out on bearing and non-bearing 15 year-old trees of cv. 'Bianca' grafted onto P. terebinthus, in a commercial pistachio orchard in Caltanissetta (Sicily). The aim of the study was to extend and improve leaf functionality by anticipating budbreak time and by sustaining leaf nitrogen level. In March 2002 and February 2003 vegetative terminal dormant buds were sprayed with 3 and 4 per cent of a solution of hydrogen-cyanamide, respectively. Foliar applications of urea were made early in the summer. The timing of budbreak was not affected by the treatment in 2002. However, shoot growing rate, number of nodes and leaf area per shoot were significantly higher on the treated shoots in comparison with the control. Nitrogen foliar applications increased leaf CO2 assimilation rate and shell dehiscence and decreased the percentage of blank nuts and fruit abnormalities.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)